Conformal terahertz absorption shielding device and preparation method thereof
By mixing carbon black with silicone rubber and vulcanized and hot-pressing to form, a conformable terahertz absorption shield is prepared, which solves the problems of high reflectivity and low absorption shielding efficiency in the prior art, and achieves an efficient terahertz wave absorption shielding effect.
Patent Information
- Application Number
- CN202411728221.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
The existing terahertz shields have problems such as high terahertz wave reflectivity and low absorption shielding efficiency, which cannot effectively solve electromagnetic interference.
Conformable terahertz absorber shield was prepared by thoroughly mixing the carbon black with the silicone rubber and adding a vulcanizing agent for vulcanization and hot-pressing.
In the terahertz band 0.5-1.0 THz, the absorption rate is greater than 99.6%, the reflectivity is less than 0.2%, and the maximum absorption shielding effect reaches more than 27.0dB, which significantly improves the absorption shielding effect of the terahertz wave.
Smart Images

Figure CN119570257A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of terahertz wave shielding, and specifically is a conformal terahertz absorption shielding device and a preparation method thereof. Background Art
[0002] In recent years, the terahertz frequency band (0.1–10THz) has become the focus of global sixth-generation (6G) wireless communications, radar detection, spectral imaging, biomedical sensing research and other promising areas. For all these applications, the system requires a method to agilely manipulate the terahertz wavefront. A wide range of electromagnetic wave functions are needed to meet the needs of creating non-line-of-sight links, directional signal enhancement, interference suppression and computational imaging. The electromagnetic interference caused by electromagnetic wave radiation is becoming more and more serious, which has an adverse effect on electronic equipment and interferes with its normal function and operation. Therefore, it is urgent to research and develop terahertz shielding media that are resistant to electromagnetic interference and have excellent shielding performance. Traditional electromagnetic interference shielding media are mainly metal materials. Although the terahertz shielding effectiveness of metal materials is good, metal materials mainly achieve reflective shielding by reflecting terahertz waves. However, this strong terahertz wave reflection will cause secondary electromagnetic pollution in the environment, and true terahertz wave shielding is not achieved. This urgently requires a more applicable method to overcome these difficulties. Anti-electromagnetic interference shielding media based on terahertz wave absorption have become the preferred development direction of terahertz wave shielding technology. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the above-mentioned background technology, and to provide a high-absorption conformable terahertz absorption shield and a preparation method thereof, so as to solve the problems of high terahertz wave reflectivity and low absorption and shielding efficiency in the existing terahertz shield.
[0004] In order to achieve the above object, the technical solution of the present invention is as follows:
[0005] In a first aspect, the present invention provides a method for preparing a conformable terahertz absorption shield, which comprises fully mixing carbon black and silicone rubber in a mass ratio of (0-8):100, adding a vulcanizing agent for vulcanization and hot pressing to obtain a terahertz absorption shield of a target shape.
[0006] As a preferred embodiment of the first aspect, the silicone rubber is methyl trifluoropropyl silicone rubber.
[0007] As a preferred embodiment of the first aspect, the mixing mass ratio of the carbon black to the silicone rubber is (2-8):100, preferably 6:100.
[0008] As a preferred embodiment of the first aspect, the vulcanizing agent is di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24S2).
[0009] As a preferred embodiment of the first aspect, the mixing mass ratio of the vulcanizing agent to the silicone rubber is (0.5-1.5):100.
[0010] As a preferred embodiment of the first aspect, the carbon black and the silicone rubber are fully mixed by mixing in an open mixing mill.
[0011] As a preferred embodiment of the first aspect, the vulcanization and hot pressing molding are both achieved by a flat-plate vulcanizer.
[0012] As a preferred embodiment of the first aspect, during the vulcanization and hot pressing process, the temperature of the flat vulcanizer is set to 150-250° C., and the pressure is set to 5 MPa-20 MPa.
[0013] As a preferred embodiment of the first aspect, during the vulcanization and hot pressing process, the hot pressing time is 5 to 20 minutes, and the exhaust needs to be evenly performed three times within 10 seconds after the start of hot pressing, and then exhausted once more 1 minute after the three exhausts are completed.
[0014] In a second aspect, the present invention provides a conformal terahertz absorption shield prepared by the preparation method described in any one of the solutions of the first aspect.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0016] The present invention vulcanizes carbon black and silicone rubber with the aid of a vulcanizing agent after being fully mixed, and hot-presses them to form a conformable terahertz absorption shield. In the 0.5-1.0THz terahertz band, the conformable terahertz absorption shield has a terahertz wave absorption rate greater than 99.6%, a reflectivity less than 0.2%, and a maximum absorption shielding effectiveness of more than 27.0dB. Carbon black particles are added to silicone rubber to form a conformable terahertz absorption shield. After the carbon black particles are dispersed in the rubber matrix, they form a conductive network. The free electrons in the carbon black particles can respond to changes in the electric field. Under the action of the terahertz wave, the movement of the charge causes the energy of the terahertz wave to be absorbed and converted into heat energy, effectively improving the absorption and shielding effectiveness of the terahertz wave, and also improving the mechanical properties of the conformable terahertz absorption shield. Silicone rubber has a certain high temperature resistance, can maintain good mechanical properties in a wide temperature range of -50°C to +250°C, and still maintains good absorption and shielding effectiveness of terahertz waves in a high temperature working environment. At the same time, bending or applying a certain external force to stretch will not cause damage to the conformable terahertz absorption shield, so it can be used in scenes where rigid materials are difficult to apply. In addition, the conformable terahertz absorption shield has the advantages of simple manufacturing process, low manufacturing cost, good absorption and shielding efficiency, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a photograph of a sample of a conformal terahertz absorption shield according to an embodiment of the present invention;
[0018] Figure 2 is a SEM photo of a sample of a conformal terahertz absorption shield in an embodiment of the present invention;
[0019] Figure 3 is a terahertz wave time domain spectrum of the conformal terahertz absorption shield in an embodiment of the present invention;
[0020] Figure 4 is a terahertz wave frequency domain spectrum of the conformal terahertz absorption shield in an embodiment of the present invention;
[0021] Figure 5 is a terahertz wave absorption coefficient curve of the conformal terahertz absorption shield in an embodiment of the present invention;
[0022] Figure 6 is a terahertz wave refractive index curve diagram of a conformal terahertz absorption shield in an embodiment of the present invention;
[0023] Figure 7 is a terahertz wave reflectivity curve diagram of a conformal terahertz absorption shield in an embodiment of the present invention;
[0024] Figure 8 It is the terahertz wave absorption and shielding effectiveness of the conformal terahertz absorption shielding device in the embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0026] In a preferred embodiment of the present invention, a method for preparing a conformable terahertz absorption shield is provided, wherein carbon black and silicone rubber are fully mixed in a mass ratio of (0-8):100, a vulcanizing agent is added for vulcanization and hot pressing to obtain a terahertz absorption shield of a target shape.
[0027] The specific materials and parameters in the preparation method of the present invention are as follows:
[0028] The above-mentioned silicone rubber can be made of methyl trifluoropropyl silicone rubber. It should be noted that in the above-mentioned preparation method, carbon black can be completely omitted. When carbon black is completely omitted, only the silicone rubber and the vulcanizing agent are vulcanized and hot-pressed. However, the present invention preferably adds carbon black, and the mixing mass ratio of carbon black to silicone rubber is (2-8):100, and the mixing mass ratio of carbon black to silicone rubber is further preferably 6:100. The above-mentioned vulcanizing agent can be di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24 S2). The mixing mass ratio of the above-mentioned vulcanizing agent to the silicone rubber is preferably (0.5-1.5):100.
[0029] The carbon black and silicone rubber are preferably fully mixed by refining in an open mill. The refining process is a process of repeatedly mixing multi-component materials in a machine to ensure the uniformity and plasticity of the materials. The above-mentioned vulcanization and hot pressing molding are preferably achieved by a flat-plate vulcanizer, and the vulcanization and hot pressing molding processes can be achieved simultaneously by a flat-plate vulcanizer. During the above-mentioned vulcanization and hot pressing molding process, the temperature of the flat-plate vulcanizer is set to 150-250°C, and the pressure is set to 5MPa-20MPa. During the above-mentioned vulcanization and hot pressing molding process, the hot pressing molding time is 5min-20min, and the air needs to be evenly exhausted three times within 10s from the start of hot pressing, and then exhausted again 1min after the three exhausts are completed.
[0030] The conformable terahertz absorption shield prepared by the above preparation method can be determined in specific shape according to the use scenario requirements. After the target shape is determined according to the actual needs, it can be processed into the corresponding shape by hot pressing. The terahertz absorption shield can be used as an attachment layer attached to the target object to be shielded to achieve the terahertz absorption shielding function. The thickness of the conformable terahertz absorption shield is preferably 2mm to 10mm.
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the above-mentioned conformal terahertz absorption shield and its preparation method are further described in detail in a specific example in combination with the embodiments below to demonstrate its technical effects.
[0032] Example
[0033] Five different conformable terahertz absorption shield samples were prepared according to the following steps:
[0034] (1) Preparation of pure silicone rubber conformal terahertz absorption shield sample:
[0035] Add di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24S2), then add a vulcanizing agent of 1% by weight of methyl trifluoropropyl silicone rubber, vulcanize and hot-press mold through a flat vulcanizer to make a thin layer of pure silicone rubber, forming a conformable terahertz absorption shield.
[0036] (2) Preparation of conformable terahertz absorption shielding device with silicone rubber and 2% carbon black:
[0037] Carbon black was added to 400 g of methyl trifluoropropyl silicone rubber, the weight of which was 2% of the weight of the methyl trifluoropropyl silicone rubber, and the mixture was fully mixed by a double-roll mill, and then a vulcanizing agent, di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24 S2), the weight of the vulcanizing agent added is 1% of the weight of the methyl trifluoropropyl silicone raw rubber, and it is vulcanized and hot-pressed on a flat-plate vulcanizer to produce a thin layer of silicone rubber with a thickness of 2.5 mm plus 2% carbon black sample. During the vulcanization and hot-pressing process, the temperature of the flat-plate vulcanizer is set to 250°C, the pressure is set to 10MPa, and the vulcanization and hot-pressing time is 20 minutes. Hot-pressing exhaust is required during the hot-pressing preparation process. The specific method is to evenly exhaust three times within 10 seconds after the start of hot pressing, and then exhaust again 1 minute after the three exhausts are completed. The optical photograph of the finally prepared silicone rubber plus 2% carbon black conformable terahertz absorption shielding device sample is shown as follows Figure 1 The corresponding SEM images of the samples are shown in Figure 2 shown.
[0038] (3) Preparation of conformable terahertz absorption shielding device with silicone rubber and 4% carbon black:
[0039] Carbon black was added to 400 g of methyl trifluoropropyl silicone rubber, the weight of which was 4% of the weight of the methyl trifluoropropyl silicone rubber, and the mixture was fully mixed by a double-roll mill, and then a vulcanizing agent, di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24 S2), the weight of the added vulcanizing agent is 1% of the weight of methyl trifluoropropyl silicone rubber, and it is vulcanized and hot-pressed on a flat vulcanizer to produce a thin layer of silicone rubber with a thickness of 2.5 mm plus 4% carbon black sample. During the vulcanization and hot-pressing process, the temperature of the flat vulcanizer is set to 250°C, the pressure is set to 10MPa, and the vulcanization and hot-pressing time is 20min. Hot-pressing exhaust is required during the hot-pressing preparation process. The specific method is to evenly exhaust three times within 10s from the start of hot pressing, and then exhaust again 1min after the three exhausts are completed to form a conformable terahertz absorption shield.
[0040] (4) Preparation of conformable terahertz absorption shielding device with silicone rubber and 6% carbon black:
[0041] Carbon black was added to 400 g of methyl trifluoropropyl silicone rubber, the weight of which was 6% of the weight of the methyl trifluoropropyl silicone rubber, and the mixture was fully mixed by a double-roll mill, and then a vulcanizing agent, di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24 S2), the weight of the added vulcanizing agent is 1% of the weight of methyl trifluoropropyl silicone rubber, and it is vulcanized and hot-pressed on a flat vulcanizer to produce a thin layer of silicone rubber with a thickness of 2.5 mm plus 6% carbon black sample. During the vulcanization and hot-pressing process, the temperature of the flat vulcanizer is set to 250°C, the pressure is set to 10MPa, and the vulcanization and hot-pressing time is 20min. Hot-pressing exhaust is required during the hot-pressing preparation process. The specific method is to evenly exhaust three times within 10s from the start of hot pressing, and then exhaust again 1min after the three exhausts are completed to form a conformable terahertz absorption shield.
[0042] (5) Preparation of conformable terahertz absorption shielding device with silicone rubber and 8% carbon black:
[0043] Carbon black was added to 400 g of methyl trifluoropropyl silicone rubber, the weight of which was 8% of the weight of the methyl trifluoropropyl silicone rubber, and the mixture was fully mixed by a double-roll mill, and then a vulcanizing agent, di-(methyl isobutyl)-diisobutyl carbon disulfide (C 12 H 24 S2), the weight of the added vulcanizing agent is 1% of the weight of methyl trifluoropropyl silicone rubber, and it is vulcanized and hot-pressed on a flat vulcanizer to make a thin layer of silicone rubber with a thickness of 2.5 mm plus 8% carbon black sample. During the vulcanization and hot-pressing process, the temperature of the flat vulcanizer is set to 250°C, the pressure is set to 10MPa, and the vulcanization and hot-pressing time is 20min. Hot-pressing exhaust is required during the hot-pressing preparation process. The specific method is to evenly exhaust three times within 10s from the start of hot pressing, and then exhaust again 1min after the three exhausts are completed to form a conformable terahertz absorption shield.
[0044] The performance test experiment was conducted on the five different conformal terahertz absorption shield samples prepared above. The terahertz wave time domain spectrum system used in the experiment was excited by a laser light source output power of 960mW with a central wavelength of 800nm, a repetition frequency of 80MHz, and a pulse width of 100 generated by a titanium sapphire femtosecond mode-locked pulse laser. The beam was divided into a stronger pump light and a weaker detection light by a beam splitter. The pump light was modulated by a chopper and focused by a lens to the photoconductive antenna gallium arsenide (GaAs) crystal to excite terahertz pulses. The terahertz pulse is collimated and incident on the sample through two off-axis metal parabolic mirrors, and then focused by another two metal parabolic mirrors to reach the 2mm thick zinc telluride ZnTe crystal, where it merges with the detection light that has passed through the delay line. At this time, the electric field of the terahertz electromagnetic radiation pulse modulates the refractive index ellipsoid of the electro-optical crystal ZnTe through the linear electro-optic effect, and the polarization state of the detection light changes accordingly. The signal is detected by a balanced diode and sent to a phase-locked amplifier for amplification. The entire time domain waveform of the terahertz signal is detected by changing the length of the delay line. The experimental test temperature is 294K, and the terahertz wave reflection and transmission spectra of the above samples are tested respectively.
[0045] The terahertz wave time domain spectra of the above five conformal terahertz absorbing and shielding dielectrics are shown in the figure below: Figure 3 As shown in the figure, the terahertz wave time domain spectra of samples with different carbon black contents are different, and the time domain peaks are slightly different. The terahertz wave time domain spectra of the five conformal terahertz absorption shielding samples are Fourier transformed to obtain the corresponding terahertz wave frequency domain spectra as shown in the figure. Figure 4 The terahertz wave absorption coefficient curves of the above five conformal terahertz absorption shield samples are shown in Figure 5 As shown in Figure 1, the terahertz wave absorption coefficients of samples with different carbon black contents are significantly different. The terahertz wave refractive index curves of the above five conformal terahertz absorption shield samples are shown in Figure 1. Figure 6 As shown in Figure 1, as the carbon black content increases from 0% to 8%, the terahertz wave refractive index of the sample decreases slightly. The terahertz wave reflectivity curves of the above five conformal terahertz absorption shield samples are shown in Figure 1. Figure 7 As shown in the figure, it can be seen that the reflectivity of all samples to terahertz waves in the 0.5-1.0THz terahertz frequency band is very low, which effectively reduces the reflection of terahertz waves. The terahertz wave absorption and shielding effectiveness of the above five conformal terahertz absorption and shielding devices are shown in the figure. Figure 8 As shown in the figure, the conformal terahertz absorption shield has a terahertz wave absorption rate of more than 99.6% in the 0.5-1.0THz terahertz band, a reflectivity of less than 0.2%, and a maximum absorption shielding effectiveness of more than 27.0dB. In terms of comprehensive performance, the best of the five medium samples is the silicone rubber plus 6% carbon black sample, which has the strongest absorption shielding effectiveness and total shielding effectiveness in the selected frequency band.
[0046] The above-described embodiments are only some preferred implementations of the present invention, but are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a conformal terahertz absorption shield, characterized in that: After carbon black and silicone rubber are fully mixed in a mass ratio of (0-8):100, a vulcanizing agent is added for vulcanization and hot pressing to obtain a terahertz absorption shielding device of a target shape.
2. The preparation method according to claim 1, characterized in that: The organic silicone rubber is methyl trifluoropropyl silicone rubber.
3. The preparation method according to claim 2, characterized in that: The mixing mass ratio of the carbon black to the silicone rubber is (2-8):100, preferably 6:
100.
4. The preparation method according to claim 2, characterized in that: The vulcanizing agent is di-(methyl isobutyl)-diisobutyl carbon disulfide.
5. The preparation method according to claim 4, characterized in that: The mixing mass ratio of the vulcanizing agent to the silicone rubber is (0.5-1.5):
100.
6. The preparation method according to claim 1, characterized in that: The carbon black and the silicone rubber are fully mixed by mixing in an open mixing mill.
7. The preparation method according to claim 1, characterized in that: The vulcanization and hot pressing molding are both achieved by a flat vulcanizing machine.
8. The preparation method according to claim 7, characterized in that: During the vulcanization and hot pressing process, the temperature of the flat vulcanizer is set to 150-250° C., and the pressure is set to 5 MPa-20 MPa.
9. The preparation method according to claim 1, characterized in that: During the vulcanization and hot pressing process, the hot pressing time is 5 to 20 minutes, and the air needs to be exhausted evenly three times within 10 seconds after the start of hot pressing, and then exhausted again 1 minute after the three exhausts are completed.
10. A conformal terahertz absorption shield prepared according to the preparation method according to any one of claims 1 to 9.